"I Did It, But Not Like That": Effects of Factually Incorrect Confessions on Juror Judgments. Issue 4 (4th July 2019) - Jones, Eric E.; Bandy, Abby D.; Palmer Jr., Phillip G.
Abstract : Several high-profile cases involving wrongful convictions have featured factually incorrect confessions (i.e., confessions that contradicted case facts). The current research investigated the effects of factually incorrect confessions on juror judgments. In Experiment 1, participants read a trial transcript, containing either no confession, a factually correct confession, or a factually incorrect confession after a 1-hour or 10-hour interrogation. Afterwards, participants judged the coerciveness of the confession, guilt of the suspect and named accomplice, and strength of the prosecution's case. Experiment 2 used confessions with different factual errors and different interrogation lengths. Participants made the same legal judgments. In both experiments, participants rated a factually incorrect confession as more coerced than a factually correct confession. Participants fully discounted factually incorrect confessions when evaluating a defendant's guilt. However, compared to conditions with no confession, participants perceived a named accomplice as guiltier and the prosecution's case as stronger when the defendant provided a factually incorrect confession.